Perancangan User Experience Aplikasi Mobile MECHANIC (Vehicle Maintenance Report) menggunakan Metode Design Thinking Studi Kasus CV. CNS (Cirebon Niaga Sejahtera) - Ath Thaariq Bhuwana Adifatha; Lutfi Fanani; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
CNS (Cirebon Niaga Sejahtera) is a CV company that is responsible for sending products from partner companies using transport vehicles. Problems experienced by CV. CNS lies in vehicle maintenance. Supervisors and drivers have difficulty in identifying the damage and finding a repair shop as a solution to the problems they are experiencing. Based on these problems, an application called MECHANIC was created which will later be able to assist users in finding a repair shop as a solution to the problems. The application design process uses the Design Thinking method where there are five stages in the implementation of this method, including Empathize, Define, Ideate, Prototype, and Test. At the testing stage, the Usability Testing method will be used to assess the learning and efficiency aspects of the designs that have been made. Then after the test, the results of the learning aspect test resulted in an average respondent's success in carrying out the task scenario of 91.5% with a failure percentage of 8.5%. Thus, it can be said that the test on the learning aspect has met the target, where the minimum target must be achieved from the percentage of respondents' success in carrying out the task scenario of 70%. Then after testing to assess efficiency, it can be said that the level of user efficiency based on time-based efficiency calculations is 0.15 goals/sec.